Tamoxifen related side effects and their impact on breast cancer incidence: A retrospective analysis of the randomised IBIS-I trial - Hale, Michael J. (Breast, 2020)
BACKGROUND: Studies in the adjuvant setting have shown that endocrine therapy related side effects predict breast cancer recurrence risk. Here, we assess the relationship between early reported side effects and incidence of breast cancer in women randomised to tamoxifen for cancer prevention in the International Breast Intervention Study (IBIS)–I trial. METHODS: Women randomised to tamoxifen in the IBIS-I trial and for whom side effect status was known at the 6-month follow-up visit were included in this analysis. Side effects included in this analysis were hot flushes, vaginal discharge, and vaginal dryness. The primary endpoint was all breast cancer and secondary endpoint was oestrogen receptor (ER) positive breast cancer. Cox proportional hazard models were used to investigate breast cancer incidence in the tamoxifen group with and without side effects reported within 6 months of randomisation. RESULTS: Women randomised to tamoxifen and reporting hot flushes at the 6-month follow-up visit had a non-statistically significant increase in breast cancer compared to those without hot flushes (HR = 1.26 (0.98–1.62), P = 0.08). A significant higher breast cancer risk was observed for postmenopausal women who reported hot flushes at the 6-month follow-up visit compared to those without hot flushes (HR = 1.59 (1.12–2.26), P = 0.01). A higher risk was observed for ER-positive breast cancer in postmenopausal women (HR = 1.81 (1.19–2.74), P = 0.01). No significant associations between gynaecological side effects and breast cancer occurrence was observed. CONCLUSIONS: Overall, no association between side effects reported at 6 months and subsequent breast cancer occurrence was observed. Some side effects might be useful markers for breast cancer occurrence in postmenopausal women.